2016
DOI: 10.1111/jpy.12395
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐nitzschia arctica sp. nov., a new cold‐water cryptic Pseudo‐nitzschia species within the P. pseudodelicatissima complex

Abstract: A new nontoxic Pseudo-nitzschia species belonging to the P. pseudodelicatissima complex, P. arctica, was isolated from different areas of the Arctic. The erection of P. arctica is mainly supported by molecular data, since the species shares identical ultrastructure with another species in the complex, P. fryxelliana, and represents a new case of crypticity within the genus. Despite their morphological similarity, the two species are not closely related in phylogenies based on LSU, ITS and rbcL. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 86 publications
3
34
0
Order By: Relevance
“…Here, we studied the phylogenetic relationships among Pseudo‐nitzschia species based on cox1 , LSU, and ITS2 phylogenies, with the inclusion of recently identified new species of Pseudo‐nitzschia , i.e., P. arctica , P. bipertita , P. limii , and P. simulans (Percopo et al. , Teng et al. , Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we studied the phylogenetic relationships among Pseudo‐nitzschia species based on cox1 , LSU, and ITS2 phylogenies, with the inclusion of recently identified new species of Pseudo‐nitzschia , i.e., P. arctica , P. bipertita , P. limii , and P. simulans (Percopo et al. , Teng et al. , Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…The number of described Pseudo-nitzschia species, as well as the number of confirmed DA producers in culture, has notably increased in the last few years (e.g., Lelong et al, 2012;Lim et al, 2013;Orive et al, 2013;Teng et al, 2016;Percopo et al, 2016). By contrast, the worldwide distribution of most of these species and their toxicity in natural populations is still poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…The genus now comprises 48 recognized species (Teng et al, 2014(Teng et al, , 2015Percopo et al, 2016), most of them described within the last two decades. Among these species, at least 23 have been mentioned as potential producers of domoic acid (DA) (Teng et al, 2015, a secondary amine neurotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, sequencing of 18S rDNA has been used to metabarcode communities of also the pico- (0.2–3 μm) and nano- (3–20 μm) sized eukaryotic fraction of Arctic marine systems (e.g., Lovejoy et al, 2006; Comeau et al, 2011; Kilias et al, 2014; Marquardt et al, 2016) as reviewed by Lovejoy (2014). The insights of arctic microbial eukaryotes gained by the use of molecular genetic tools include the identification of ecotypes endemic to the Arctic (Lovejoy et al, 2007; Terrado et al, 2013; Percopo et al, 2016), the existence of taxa-specific biogeographic patterns (Thaler et al, 2015), and a linking of distinct protist assemblages to water masses (Hamilton et al, 2008; Bachy et al, 2011; Monier et al, 2014; Metfies et al, 2016). It has been shown that the pronounced Arctic seasonality extends to the succession of microbial eukaryotes (Marquardt et al, 2016; Joli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%